2004
DOI: 10.1016/s0966-6362(03)00060-2
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle negotiation kinematics: age-dependent effects of postural threat

Abstract: DEDICATIONI dedicate this thesis to my Poppa, John Joseph Lacey. You have taught me the meaning of dignity.iii ABSTRACTThe effects of postural threat and the potential consequences of obstacle contact on the obstacle negotiation kinematics among younger and older adults were examined. Seventeen older (OA; 7 males, 10 females; mean age, 68.94 ± 4.85) and fifteen younger adults (YA; 5 males, 10 females; mean age, 22.53 ± 2.77) negotiated virtual and real obstacles while walking at a self-determined velocity alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 50 publications
(144 reference statements)
2
48
1
3
Order By: Relevance
“…Similar to unobstructed level ground walking this coincided with an increased gait speed and a tendency toward an increase in step length. The latter findings appears to be in contrast with previous studies on obstacle crossing in which it was found that step length and gait speed decreased in the presence of a postural threat [27]. This suggests that the present findings cannot simply be interpreted as the consequence of an increase in postural threat experienced due to leg muscle fatigue, but are more specific to the fatigue experienced by the individual during the experiment.…”
Section: Obstacle Crossing During Walkingcontrasting
confidence: 56%
“…Similar to unobstructed level ground walking this coincided with an increased gait speed and a tendency toward an increase in step length. The latter findings appears to be in contrast with previous studies on obstacle crossing in which it was found that step length and gait speed decreased in the presence of a postural threat [27]. This suggests that the present findings cannot simply be interpreted as the consequence of an increase in postural threat experienced due to leg muscle fatigue, but are more specific to the fatigue experienced by the individual during the experiment.…”
Section: Obstacle Crossing During Walkingcontrasting
confidence: 56%
“…Of the 13 studies that reported spatiotemporal data, five reported no difference in spatiotemporal variables between young and older adults [17,[22][23][24][25]. In the eight that reported differences, older adults walked slower during obstacle crossing [13,14,15,20,21,26], with smaller steps [13,14,18,21]. Older adults landed closer to the obstacle with their lead limb after crossing in three studies [14,21] however, only a significant difference between older and younger females was reported in the study by Chen et al [20].…”
Section: Spatiotemporal Adaptations During Obstacle Crossingmentioning
confidence: 83%
“…Stepping is necessary if there is sufficiently high velocity of the COM, even if the COM is located within the BOS at step initiation. Older adults employ a rapid stepping response compared to young adults under the same conditions because such stepping responses are less threatening to loss of balance [29,38].…”
Section: Responses To Perturbationmentioning
confidence: 98%